Museum Pieces: Toward the Indigenization of Canadian Museums - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's University Press, 2011)
Ruth Phillips argues that these practices are "indigenous" not only because they originate in Aboriginal activism but because they draw on a distinctively Canadian preference for compromise and tolerance for ambiguity. Phillips dissects seminal exhibitions of Indigenous art to show how changes in display, curatorial voice, and authority stem from broad social, economic, and political forces outside the museum and moves beyond Canadian institutions and practices to discuss historically interrelated developments and exhibitions in the United States, Britain, Australia, and elsewhere. Drawing on forty years of experience as an art historian, curator, exhibition critic, and museum director, she emphasizes the complex and situated nature of the problems that face museums, introducing new perspectives on controversial exhibitions and moments of contestation. A manifesto that calls on us to re-imagine the museum as a place to embrace global interconnectedness, Museum Pieces emphasizes the transformative power of museum controversy and analyses shifting ideas about art, authenticity, and power in the modern museum.
Section: xvi, 376 p., [16] p. de pl. : ill. (certaines en coul.).
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé